Solid state chemistry - Solid state chemistry; Cheetham, A. K.; Day, P. ([S.l.] : Clarendon Press, 1990)
A rapidly expanding branch of science, solid-state chemistry grows in importance as scientists recognize its relevance to subjects as diverse as optoelectronics and heterogeneous catalysis. The first of two volumes, this book concentrates on methods for preparing solids and for studying structures and physical properties. Among the methods described here are diffraction and vibrational, electronic, and photoelectron spectroscopies. Bulk measurements such as conductivity, magnetic susceptibility, and calorimetry are also described, along with theoretical modeling of crystal structures.
Keywords: chemistry,solid state